Armed Banditry and National Security in Nigeria: An Exploratory Analysis - MADUBUEGWU, Chibuike E; ABAH, Nobert Chijioke (Socialscientia: Journal of Social Sciences and Humanities, 2024)
The North-West, an area of 216,065sq of the country’s total land mass with projected population of over 50 million people who are predominantly farmers, pastoralists and agro-pastoralists, is today ravaged by unabated menace of armed bandits and criminal gangs. In reference to this unpleasant situation, this paper examined extensively the dynamics and trends of armed banditry in the North-West region as a potential threat to national security. The methodology of the paper is qualitative design which illuminate the import of documentary sources of data collection (with emphasis on reports of international agencies, texts, articles, official bulletins), and non-participant observation of media coverage of events to textual-analyze the underlying issues and fundamentals of bandit insurgency in states of North-West region. The work revealed the existence of over 10,000 thousands armed bandits operating in rural communities and forests across Zamfara, Kastina, Kaduna and Sokoto states whose peril have led to over 50,000 thousands deaths; 210, 354 thousand people internally displaced from approximate 200 towns, 34,316 hectares of farmlands rendered inaccessible or (lost to bandits) and over 300 thousand livestock stolen from 2011 to 2021 occasioned with the abduction of 1, 436 school children from January to October 2021, as government and security agencies work fanatically to stem the tide. To complement the ongoing efforts, the discourse recommends national security summit to leverage on resourceful knowledge for holistic approach, inter-agency collaboration, and synergized roles as among the fundamentals to respond more efficiently to armed banditry in the North-West.